Pengaruh Pengetahuan Investasi dan Motivasi Investasi Terhadap Minat Berinvestasi Mahasiswa Pendidikan Ekonomi Fakultas Ekonomi Universitas Negeri Padang - Iqtal Amhalmad1; Agus Irianto (Jurnal Ecogen, 2019)
This study aims to determine the effect of investment knowledge and investment motivation on investment interests of students Economic Education, Economics Faculty, Padang State University. This type of research is descriptive and associative. The population of this study were 411 students from the Economics Faculty, Padang State University, 2016-1018. The sampling technique is Propositional Random Sampling with a sample of 80 students. The analysis technique used is path analysis "Path Analysis". The results showed that: 1) Investment knowledge has a significant effect on investment motivation of students of Economic Education Faculty of Economics, State University of Padang 2) Knowledge of investment has a significant effect on investment interests of students Economics Faculty of Economics, State University of Padang 4) Investment knowledge and investment motivation have a significant effect on the investment interests of students of Economic Education at State University of Padang. Keywords: investment knowledge, investment motivation and investment interest